PERENCANAAN PENDIDIKAN DALAM MENUMBUHKAN KECINTAAN MEMBACA AL-QUR’AN DI GAMPONG CEUMPEDAK KECAMATAN COT GIREK - Saputra, Andika (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2024)
Religious knowledge is a science that every Muslim, male and female, must be able to read the Koran, this is the beginning of education that must be given by parents to children, so the author is very interested in raising a title